Sexual reproducion of Quercus macdougallii, an endemic oak of Sierra Juárez, Oaxaca - Clark-Tapia, Ricardo; Mendoza Ochoa, Ana; Aguirre-Hidalgo, Víctor; Antúnez, Pablo; Campos Contreras, Jorge Eduardo; Valencia-A., Susana; Luna-Krauletz, María Delfina; Alfonso-Corrado, Cecilia Liana (Instituto de Ecología, A.C., 2018)
Quercus macdougallii Martínez is an endemic and threatened species of the Sierra Juárez, Oaxaca. Effective conservation and restoration programs that ensure long-term in situ populations are needed in the region. Therefore, an important aspect to consider is adequate knowledge of how to reproduce this species, specifically, knowledge of the ecology of seeds and seedlings. The objective of this study was to evaluate the sexual reproduction (acorn) of this species, in order to generate recommendations for its conservation. Seed production from 2009 to 2010 was recorded as well as seed depredation, seed parasitism, germination percentage and survival of seedling coming from seeds of three different sizes-classes. The objetives one and two were evaluated in the laboratory and in the field, while the objetive three was analysed in the laboratory. Results showed that the species had an average yield per tree of 1735 ± 832 seeds, low depretation (< 7%) and low parasitation rates (8.7%). Seed germination and seedling growth in the field and in the laboratory were higher in large (> 1.701 g) than in medium (1.045 g - 1.70 g) and smaller seeds (0.350 g - 1.044 g), with a mean germination percentage of 50 %. Seedling survival was 10% in the disturbed site and 75% in the undisturbed site. It is recommended to collect large seeds for reforestation programs. To do this, it is advisable to germinate acorns in the laboratory, let them grow for six months and transplant them at the beginning of the rainy season under the canopy trees.